A novel ruthenium(II)–polypyridyl complex inhibits cell proliferation and induces cell apoptosis by impairing DNA damage repair. (August 2014) - Yang, Qingyuan; Zhang, Zhao; Mei, Wenjie; Sun, Fenyong
Abstract : Ruthenium complexes are widely recognized as one of the most promising DNA damaging chemotherapeutic drugs. The main goal of this study was to explore the anticancer activity and underlying mechanisms of [Ru(phen)2 ( p -BrPIP)](ClO4 )2, a novel chemically synthesized ruthenium (Ru) complex. To this end, we employed MTT assays to determine the anticancer activity of the complex, and performed single-cell gel electrophoresis (SCGE) and Western blotting to evaluate DNA damage. Our results showed that the Ru(II)–poly complex caused severe DNA damage, possibly by downregulating key factors involved in DNA repair pathways, such as proliferating cell nuclear antigen (PCNA) and ring finger protein 8 (RNF8). In addition, this complex induced cell apoptosis by upregulating both p21 and p53. Taken together, our findings demonstrate that the Ru(II)–poly complex exhibits antitumour activity by inducing cell apoptosis, which results from the accumulation of large amounts of unrepaired DNA damage.